Subcategorization of the AUS/FLUS Thyroid Nodule Based on the 2017 Bethesda System at Dr. Cipto Mangunkusumo Hospital from 2018-2021 - Linggodigdo, Michelle; Rachmadi, Lisnawati (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
IntroductionThe AUS/FLUS (Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance) category is one of the most challenging diagnoses in thyroid fine-needle aspiration biopsy (FNAB) for pathologists. This is due to the heterogeneous cytomorphological features with low Risk of Malignancy (ROM) accuracy, which is crucial to determining further management. The 2017 Bethesda System introduced subcategorization of AUS/FLUS to improve ROM accuracy. However, the widespread adoption of this subcategorization remains limited. MethodsA retrospective analytical cross-sectional study was carried out using secondary data of thyroid FNAB cases diagnosed with AUS/FLUS followed by surgical procedures at the Department of Anatomical Pathology, Faculty of Medicine, University Indonesia/Dr. Cipto Mangunkusumo Hospital from 2018 to 2021. Furthermore, a review and subcategorization into AUS-C1 (focal nuclear atypia), AUS-C2 (mild nuclear atypia), AUS-A (architectural atypia), AUS-C&A (nuclear and architectural atypia), AUS-H (Hűrthle cell aspiration), AUS-NOS (atypia not otherwise specified), and AUS-L (lymphoid cell atypia other than lymphoma) was performed. ResultAmong a total of 2,082 patients, 599 (28.7%) were diagnosed as AUS/FLUS. There were 75 patients with AUS/FLUS who proceeded with surgery, while 64 (85.3%) showed malignancy. The most common subcategory was AUS-C1 (60%), followed by AUS-NOS (21.3%), AUS-C&A (9.3%), AUS-C2 (8%), and AUS-H (1.4%). ROM subcategory AUS-C1 was significantly higher compared to AUS-C2 (p=0.009) and AUS-NOS (p=0.011). Conclusion The percentage of AUS/FLUS diagnoses at Dr. Cipto Mangunkusumo Hospital from 2018 to 2021 was 28.7% with ROM ranging from 10.6% to 85.3%. There was a significant difference in ROM between AUS-C1 and AUS-C2, as well as AUS-C1 and AUS-NOS. Therefore, it was concluded that AUS-C1 thyroid nodules with or without architectural atypia require more aggressive management compared to those with AUS-C2 and AUS-NOS features.